Impact of genotype in relapsed and refractory acute myeloid leukaemia patients treated with clofarabine and cytarabine: a retrospective study. (18th June 2019) - Mondesir, Johanna; Alary, Anne‐Sophie; Sibon, David; Willems, Lise; Deau, Benedicte; Suarez, Felipe; Hermine, Olivier; Fontenay, Michaela; Bouscary, Didier; Kosmider, Olivier; Tamburini, Jerome
Summary: The treatment of relapsed/refractory (R/R) acute myeloid leukaemia (AML) remains a challenge. Among salvage chemotherapy regimens, the clofarabine and cytarabine (CLARA) combination has been widely evaluated and has a favourable safety/efficacy balance. Predictive factors of efficacy in patients with R/R AML are unclear, particularly the impact of AML‐related gene mutations. We report our single‐centre experience on 34 R/R AML patients treated with CLARA, with a focus on the genetic characterization of our cohort. CLARA yielded a 47% response rate among this poor‐prognosis AML population, while two patients (5·8%) died due to treatment‐related toxicity. The two‐year progression‐free survival and overall survival rates were 29·4% and 35·3%, respectively. Nine patients (26%) had long‐term response with a median follow‐up of 39·5 months among the responders, of whom six underwent haematopoietic stem cell transplantation. Adverse karyotype did not correlate with response or survival, and secondary AML were more frequent among responders to CLARA, suggesting that this combination may successfully salvage R/R AML patients regardless of adverse prognostic markers. We also observed that a low mutational burden and absence of splice mutations correlated with prolonged survival after CLARA, suggesting that extensive genotyping may have prognostic implications in R/R AML.